(Un)settled sojourners in cities: the scalar and temporal dimensions of migrant precarity. Issue 20 (16th December 2021) - Chacko, Elizabeth; Price, Marie
ABSTRACT: In this Special issue, we focus on temporary migrants as an important and often overlooked demographic in urban areas around the world. We demonstrate through empirical evidence that these migrants experience oscillations in precarity over time and that these fluctuations are mediated and better understood through a sensitivity to different scales and scalar processes. Most migration policies are created by national governments that privilege certain categories of migrants (such as high-skilled professionals or international students) over others (such as low-skilled or asylum seekers). However, the lived experience of many temporary migrants plays out in the households, neighbourhoods, and cities in which they reside and work. Temporary migrant precarity is also influenced by policies and practices shaped by local urban governments and civil society. Thus, temporary migrants are subject to intersecting and varied levels of temporal and scalar precarity, often compounded by personal and social attributes. Finally, we demonstrate that many temporary migrants employ individual and collective agency to resist their categorisation as disposable and transitory workers.